Exchange Rate Pass-Through in a Competitive Model of Pricing-to-Market - AUER, RAPHAEL; CHANEY, THOMAS (Journal of money, credit and banking, 2009)
This paper extends the Mussa and Rosen (1978) model of quality pricing under perfect competition. Exporters sell goods of different qualities to consumers who have heterogeneous preferences for quality. Production is subject to decreasing returns to scale and, therefore, supply and the toughness of competition react to cost changes brought about by exchange rate fluctuations. First, we predict that exchange rate shocks are imperfectly passed through into prices. Second, prices of low-quality goods are more sensitive to exchange rate shocks than prices of high-quality goods. Third, in response to an exchange rate appreciation, the composition of exports shifts toward higher quality and more expensive goods. We test these predictions using highly disaggregated price and quantity U.S. import data and find only weak empirical evidence in support of our theory.